Relevance of intersubjectivity for understanding the low self-esteem of nursing students - Santos, Laís Vasconcelos; Dantas, Juliane Rangel; Santos, Viviane Euzébia Pereira; Lira, Ana Luisa Brandão de Carvalho (Revista de Enfermagem da UFPI, 2024)
Objective: To reflect on the low self-esteem of nursing students in the light of the theoretical framework of the philosopher Alfred Schütz. Methods: This is a theoretical-reflective study, based on scientific literature and authorial experience as a research resource, developed from September to December 2020. Results: The self-esteem phenomenon can be seen through an intersubjective dimension, making it possible to understand the influence of life contexts (personal, social, professional) and academic experiences on the psychic illness of nursing students. Low self-esteem can impair academic performance, interpersonal relationships, and quality of life. And also cause self-destructive behavior, lower self-efficacy and abandonment of the course. Conclusion: Recognizing the intersubjectivity in this phenomenon enables the awakening and encouragement for discussions about the factors that affect psychological well-being and helps in the process of identifying the human responses of students with low self-esteem and planning comprehensive and holistic care.